2017
DOI: 10.5935/0004-2749.20170037
|View full text |Cite
|
Sign up to set email alerts
|

Corneal backscatter in insulin-dependent and non-insulin-dependent diabetes mellitus patients: a pilot study

Abstract: Diabetic patients showed higher values of corneal light backscatter than healthy subjects. Corneal optical density analysis may be a useful tool for monitoring and assessing the ocular changes caused by diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…As far as CCT is concerned, there was no statistically significant difference between patients with DM and controls in our study, in line with several authors [8,11,22,23], although most of the existing studies have controversial results, showing an increase of CCT in diabetic patients [9,10,[12][13][14][15][16][17][18][19][20]. We also did not find any correlation between CCT and patients' characteristics; i.e., DM duration, HbA1c levels, disease severity, as it was found for ECD, which was in line with Toygar et al [24], who also suggested that retinal disease severity does not seem to have an effect on CCT.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As far as CCT is concerned, there was no statistically significant difference between patients with DM and controls in our study, in line with several authors [8,11,22,23], although most of the existing studies have controversial results, showing an increase of CCT in diabetic patients [9,10,[12][13][14][15][16][17][18][19][20]. We also did not find any correlation between CCT and patients' characteristics; i.e., DM duration, HbA1c levels, disease severity, as it was found for ECD, which was in line with Toygar et al [24], who also suggested that retinal disease severity does not seem to have an effect on CCT.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings regarding ECD de- crease were in accordance with the majority of previous studies. Specifically, Inoue et al [11] found a 4.1% reduction in ECD in patients with DM compared to controls in line with other authors, who also reported a significant reduction in ECD in diabetic patients [9,10,[14][15][16][17][18][19][20]. However, there is no absolute consensus in the literature.…”
Section: Discussionmentioning
confidence: 76%
“…Gao et al [123] used Pentacam HRto assess CCT, COD, and alterations of corneal transparency in 180 diabetes patients; they found an increase in COD and CCT compared with controls, with a positive association between the medial and intimal COD and central CCT in diabetes patients. In addition, Calvo-Maroto et al [124], in a pilot study in adult diabetes patients, showed higher values of corneal light backscatter in patients with diabetes when compared with healthy subjects. However, COD values in children with T1D were similar in all concentric zones and layers to those in healthy children [125].…”
Section: Diabetes and Corneal Stromamentioning
confidence: 99%
“…Studies have assessed changes in various aspects of the anterior segment during bouts of hyperglycemia and after controlling for the disease, but the effects of DM on corneal topography and aberrometry have not been widely studied. Table 2 summarizes the mean Pentacam parameters for aberrometry, keratometry, and corneal asphericity of patients with DM in the literature [11,15,[22][23][24][25][26][27][28][29][30], with the corresponding values in non-diabetic eyes [11,23,[25][26][27][28][29][30][31][32][33][34][35][36]. However, to the best of our knowledge, no study has reported the RMS of the LOAs or HOAs, or magnitude of posterior topographic astigmatism in eyes with type 1 DM (T1DM) or T2DM.…”
Section: Discussionmentioning
confidence: 99%